Astragaloside IV alleviated bone loss in mice with ovariectomy-induced osteoporosis via modulating gut microbiota and fecal metabolism - Wang, Huichao; Huang, Zhongyue; Chen, Guangnan; Li, Yang; Liu, Youwen; Gu, Huijie; Cao, Yujing (Frontiers in Pharmacology, 2025)
BackgroundAstragaloside IV (AS-IV) is one of the most potent components of Astragalus. It has been reported to promote bone formation and inhibit osteoclastogenesis, suggesting its potential as a candidate for the prevention and treatment of postmenopausal osteoporosis (PMOP). The gut microbiota may play a crucial role in mediating the effects of AS-IV.ObjectiveTo investigate the impact of gut microbiota on the efficacy of AS-IV in treating PMOP.MethodsMice were randomly divided into three groups: Sham, ovariectomy (OVX), and AS-IV-treated OVX group (80 mg/kg). Bone loss was evaluated using Micro-CT and histopathology. Immunohistochemistry assessed specific bone markers. Inflammatory levels were measured by enzyme-linked immunosorbent assay (ELISA). Intestinal barrier function was examined via colonic histopathology and immunohistochemistry. Gut microbiota composition was analyzed by 16S rDNA sequencing, while metabolomic profiling identified key metabolites. Correlation analysis was performed to explore relationships between differential bacteria, key metabolites, and bone loss.ResultsAS-IV improved the femur microarchitecture and modulated bone turnover in OVX mice. AS-IV treatment strengthened the intestinal barrier function and decreased gut permeability. This compound reduced colonic oxidative stress and serum and bone marrow inflammatory cytokine production. 16S rDNA sequencing revealed that AS-IV modulated the gut microbiota composition, while metabolomic analysis showed its effects on pathways related to hormone biosynthesis, D-amino acid metabolism, and galactose metabolism.ConclusionThis study provides new insights into the use of AS-IV for treating PMOP, highlighting the gut microbiota and its metabolites as key regulatory factors in AS-IV’s therapeutic effects.